Sosialisasi Tata Cara Pengisian Beban Kerja Dosen/Laporan Kinerja Dosen pada Platform Sistem Informasi Sumberdaya Terintegrasi (SISTER) untuk Dosen Pemula - Ersyafdi, Ilham Ramadhan; Prabowo, Muhammad Aras; Aryani, Habsyah Fitri; Ulfah, Fitriah; Fauziyyah, Nurul; Ahmadi, Lusiana Putri; Khomsatun, Siti (Ikatan Cendekiawan Muda Akuntansi, 2025)
One of the important parts of the higher education system is lecturers who have very important responsibilities, duties and roles in achieving national education goals. Lecturer certification aims to improve the quality of national education and the welfare of teaching staff by encouraging them to further improve their professionalism. To obtain certification as a lecturer, a lecturer must fulfill a minimum of twelve credits per semester for two consecutive years through the Lecturer Workload (BKD). BKD is a description of the lecturer's SKS load to carry out the Tri Dharma in the next semester. However, the problem in the field is that many lecturers still do not know the importance of filling in and the procedures for BKD. The target of this Community Service (PKM) activity is novice lecturers who have not been certified so that they can fill in BKD on the SISTER platform independently. It is also hoped that after participating in this activity, novice lecturers will be aware of preparing all forms of complete documents used as attachments for proof of filling.